Design and Analysis of Jacket Substructures for Offshore Wind Turbines - I-Wen Chen (Energies, 2016)
This study focused on investigating various existing types of offshore jacket substructures along with a proposed twisted-tripod jacket type (modified jacket (MJ)-structures). The architectures of the three-leg structure, as well as the patented twisted jacket structure motivated the design of the proposed MJ-structures. The dimensions of the structures were designed iteratively using static stress analysis to ensure that all structures had a similar level of load-carrying capability. The numerical global buckling analyses were performed for all structures after the validation by the scaled-down experiments. The local buckling strength of all compressive members was analyzed using the NORSOK standard. The results showed that the proposed MJ-structures possess excellent structural behavior and few structural nodes and components competitive with the patented twisted jacket structures, while still maintaining the advantages of low material usage similar to the three-leg jacket structures. This study provides alternatives for the initial selection and design of offshore wind turbine substructures for green energy applications.